Tumor necrosis factor alpha gene regulation in activated T cells involves ATF-2/Jun and NFATp. - Tsai, E Y (1996)
The human tumor necrosis factor alpha (TNF-alpha) gene is one of the earliest genes expressed upon the activation of a T or B cell through its antigen receptor. Previous experiments have demonstrated that in stimulated T cells, a TNF-alpha promoter element, kappa 3, which binds NFATp, is required for the cyclosporin A-sensitive transcriptional activation of the gene. Here, we demonstrate that a cyclic AMP response element (CRE), which lies immediately upstream of the kappa 3 site, is also required for induction of TNF-alpha gene transcription in T cells stimulated by calcium ionophore or T-cell receptor ligands. The CRE binds ATF-2 and Jun proteins in association with NFATp bound to kappa 3. These proteins bind noncooperatively in vitro; however, the transcriptional activity of the CRE/kappa 3 composite site is dramatically higher than the activity of the kappa 3 site alone, indicating that the two sites cooperate in vivo. This study is the first demonstration of a role for ATF-2 in TNF-alpha gene transcription and of a functional interaction between ATF-2/Jun and NFATp. This novel pairing of NFATp with ATF-2/Jun may account for the specific and immediate pattern of TNF-alpha gene transcription in stimulated T cells.